2020
DOI: 10.1186/s13287-020-1566-5
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic fields potentiate the paracrine function of mesenchymal stem cells for cartilage regeneration

Abstract: Background: The mesenchymal stem cell (MSC) secretome, via the combined actions of its plethora of biologically active factors, is capable of orchestrating the regenerative responses of numerous tissues by both eliciting and amplifying biological responses within recipient cells. MSCs are "environmentally responsive" to local micro-environmental cues and biophysical perturbations, influencing their differentiation as well as secretion of bioactive factors. We have previously shown that exposures of MSCs to pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 68 publications
0
64
0
Order By: Relevance
“…Human umbilical cord-derived MSCs (HucMSCs) have higher proliferative potential and lower immunogenicity compared with those of other MSCs and have become an ideal choice in treating diabetes [7][8][9]. Increasing evidence has shown that MSCs exert therapeutic effects mainly through paracrine signaling [10]. As an important manifestation of paracrine signaling, exosomes have been considered to represent a promising cell-free therapy due to their multiple bioactivities and intercellular communication functions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Human umbilical cord-derived MSCs (HucMSCs) have higher proliferative potential and lower immunogenicity compared with those of other MSCs and have become an ideal choice in treating diabetes [7][8][9]. Increasing evidence has shown that MSCs exert therapeutic effects mainly through paracrine signaling [10]. As an important manifestation of paracrine signaling, exosomes have been considered to represent a promising cell-free therapy due to their multiple bioactivities and intercellular communication functions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…[5] The function of the cellular secretome is responsive to mitochondrial activation [57] and has recently been shown to be stimulated by the same magnetic field paradigm employed in this study. [58] Cell senescence moreover, is characterized by a senescence associated secretory phenotype [2][3][4] that is capable of inducing a contagious state of senescence to neighboring cells and tissues. [59] Therefore, given the enrichment of the healthy muscle secretome for diffusible factors, collectively known as myokines, possessing systemwide therapeutic and regenerative properties, [60][61][62] the possibility of activating, reinstating or fortifying the myokine response in muscle with CDVs derived from proliferative muscle cells in combination with magnetic field therapy merits further consideration.…”
Section: (9 Of 13)mentioning
confidence: 99%
“…PEMF Device: The PEMF device used in this study has been previously described. [5,20,58] All samples were exposed once for 10 min at a field amplitude of 1.5 mT. All PEMF-treated samples were compared to time-matched control samples (0 mT) that were manipulated in exactly the same as experimental samples, including placement into the PEMFgenerating apparatus for the designated time, except that the apparatus was not set to generate a magnetic field.…”
Section: (10 Of 13)mentioning
confidence: 99%
“…MSC transplantation is a fast-developing therapy in cell-based therapies and regenerative medicine [ 8 10 ]. Thus, they are regarded as a promising candidate for the repair and regeneration of some diseases [ 6 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%